2011
DOI: 10.1002/ddrr.1110
|View full text |Cite
|
Sign up to set email alerts
|

Early Language Delay and Specific Language Impairment

Abstract: Early language delay (ELD) is a warning sign that may presage the presence of a later language impairment (LI). In order to allow more targeted identification and earlier intervention for LI, better diagnostic measures for toddlers are needed. Development of accurate predictive/diagnostic models requires consideration of a set of complex interrelated questions around definition, causality, and theories of LIs. A multifactorial model of language development and LI is essential to increase the accuracy of predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 126 publications
(154 reference statements)
2
21
0
2
Order By: Relevance
“…Elements with relatively low semantic and perceptual salience, such as articles, prepositions, auxiliaries and obligatory infinitives, are frequently missing, as in the following examples: THEY SINGING (Binger et al, 2011); I CHANGE SCHOOLS SEPTEMBER (Lund & Light, 2007b); and "Do you want watch" (Lund & Light, 2003). These error patterns are similar to those reported in speaking children with language impairments (Moyle, Stokes, & Klee, 2011). Given the low semantic valence and the potential effort involved in their production, such omissions may at least in part reflect strategic efficiency.…”
Section: Running Head: Language Development and Aided Communication 15supporting
confidence: 60%
“…Elements with relatively low semantic and perceptual salience, such as articles, prepositions, auxiliaries and obligatory infinitives, are frequently missing, as in the following examples: THEY SINGING (Binger et al, 2011); I CHANGE SCHOOLS SEPTEMBER (Lund & Light, 2007b); and "Do you want watch" (Lund & Light, 2003). These error patterns are similar to those reported in speaking children with language impairments (Moyle, Stokes, & Klee, 2011). Given the low semantic valence and the potential effort involved in their production, such omissions may at least in part reflect strategic efficiency.…”
Section: Running Head: Language Development and Aided Communication 15supporting
confidence: 60%
“…Bishop and Leonard (2000) reported that children with SLI fall at the bottom end of the normal distribution of language competence (3). Practically, a child who has a language impairment in the absence of a significant sensory, psychiatric, neurological, or intellectual disorder is diagnosed with SLI (4,5); In other words, as Schwartz (2009) explained, "SLI is an impairment of language comprehension, language production, or both in the absence of hearing impairment, the absence of a general developmental delay (i.e., a normal performance IQ), the absence of any neurological impairment (e.g., perinatal bleeds, seizure disorders), and no diagnosis of autism" (6). Tomblin et al (1996) were the first to provide a valid and reliable diagnostic system labeled the EpiSLI system for the conduct of epidemiologic research on specific language impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In developmental (specific) language impairment predominantly a single developmental domain is affected, although longitudinal studies provided evidence that the delay may not be solely restricted to the language domain over time. 1,91 This disorder is supposed to be the result of an interplay between genetic, environmental, neurobiological and cognitive (perception, speed of processing, working memory and phonological short-term memory) factors. 91,92 Developmental language impairment is a heterogeneous disorder with various subgroups and a changing profile for each individual across development.…”
mentioning
confidence: 99%
“…1,91 This disorder is supposed to be the result of an interplay between genetic, environmental, neurobiological and cognitive (perception, speed of processing, working memory and phonological short-term memory) factors. 91,92 Developmental language impairment is a heterogeneous disorder with various subgroups and a changing profile for each individual across development. 91 The prevalence of specific language impairment was estimated as 7.4% among kindergarten children in the USA.…”
mentioning
confidence: 99%
See 1 more Smart Citation